(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article explores how the Shanghai Cooperation Organization (SCO) has developed since its creation in 2001 and examines the impact of its expansion on the organization’s internal balance and agenda. By analyzing current trends and the strategic approaches of its key member states, the article outlines potential scenarios for the SCO’s future transformation. The Shanghai Cooperation Organization (SCO) has seen significant changes since it was founded in 2001. Originally established by China, Russia, Kazakhstan, Kyrgyzstan, Tajikistan, and Uzbekistan, the SCO aimed to address regional security issues, promote economic cooperation, and build mutual trust among its members. Over the years, the organization has expanded its scope and influence, especially with the addition of India and Pakistan as full members in 2017. This expansion has introduced new dynamics, challenging the internal balance and prompting a reassessment of the SCO’s strategic goals. This article examines the various trends that have shaped the SCO’s development, focusing on how the organization has adapted to a changing geopolitical landscape. The inclusion of new members has not only increased the SCO’s geopolitical significance but also brought in diverse perspectives and interests, complicating decision-making processes and influencing the organization’s agenda. Looking ahead, the article considers several potential scenarios for the SCO’s future. One possibility is that the SCO continues to expand, bringing in more members and enhancing its global influence and ability to address transnational issues. Another scenario envisions internal divisions leading to a more fragmented organization, where differing national interests hinder unified action. A third scenario considers the potential for the SCO to evolve into a more formalized and structured entity, with clearer mechanisms for conflict resolution and cooperation. By examining the strategic approaches of key member states, particularly China and Russia, the article provides insights into how the SCO might navigate its internal challenges and leverage its strengths to remain a relevant and effective regional organization.